The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/jcdd9100319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anisotropic Electrical Conductivity Induced by Fiber Orientation on Ablation Characteristics of Pulsed Field Ablation in Atrial Fibrillation Treatment: A Computational Study

Abstract: Pulsed field ablation (PFA) is a promising new ablation modality for the treatment of atrial fibrillation (AF); however, the effect of fiber orientation on the ablation characteristics of PFA in AF treatment is still unclear, which is likely an essential factor in influencing the ablation characteristics. This study constructed an anatomy-based left atrium (LA) model incorporating fiber orientation and selected various electrical conductivity and ablation targets to investigate the effect of anisotropic electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This implies a degree of anisotropy of only 11% in terms of electrical conductivity at low frequencies, which probably has a minimal impact on ablation modeling. Differences of around 26% were reported by Gabriel et al [25] at 40-70 Hz in three different directions, which implies an anisotropy ratio of 1.27, and much lower than those assumed by Zang et al [13] (between 1.43 and 6.25) in a computational PFA modeling study, who did find differences in terms of the lesion size induced by PFA between an isotropic and anisotropic model.…”
Section: Limitationsmentioning
confidence: 55%
“…This implies a degree of anisotropy of only 11% in terms of electrical conductivity at low frequencies, which probably has a minimal impact on ablation modeling. Differences of around 26% were reported by Gabriel et al [25] at 40-70 Hz in three different directions, which implies an anisotropy ratio of 1.27, and much lower than those assumed by Zang et al [13] (between 1.43 and 6.25) in a computational PFA modeling study, who did find differences in terms of the lesion size induced by PFA between an isotropic and anisotropic model.…”
Section: Limitationsmentioning
confidence: 55%
“…Physical field parameter simulation research is an important stage in the clinical application of new technologies, and reasonable PFA parameters will substantially reduce the cost of clinical research [ 37 , 44 , 74 ]. The researchers obtained a simplified cardiac model from between models of different complexities that can get more accurate simulation results, which provides data support for reducing the complexity of the model in the future.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…The results showed that the difference in surface ablation area between anisotropic and isotropic conductivity was greater than 73.71%, and the percentage difference in ablation volume size was greater than 6.9%. It was shown that in left atrial ablation, anisotropic conductivity can be used for pulsed-field ablation if the same area and depth are considered [ 44 ]. PFA is classified as a non-thermal ablation technique, and the rise in tissue temperature is directly correlated with the heart’s blood flow.…”
Section: Pulsed Electric Field Ablation: Simulation Parameter Researchmentioning
confidence: 99%
“…Another increasingly important application of electroporation in biomedicine is treatment of cardiac arrhythmias, particularly of atrial fibrillation, by ablation of pulmonary vein tissue using irreversible electroporation [10], [15]- [18]. The specific structure of skeletal and cardiac muscles dictates an anisotropic electrical conductivity, leading to a fibre-orientation dependent electric field distribution upon pulse application [19]- [21]. The electrical conductivity of skeletal muscle in the direction of its fibres was found to be higher than the electrical conductivity in the direction perpendicular to the fibres [22]- [27].…”
Section: Introductionmentioning
confidence: 99%